Prevalence and characteristics of transverse myelitis and neuromyelitis optica spectrum disorders in the United Arab Emirates: A multicenter, retrospective study. Issue 3 (7th May 2018) - Holroyd, Kathryn B.; Aziz, Faisal; Szolics, Miklos; Alsaadi, Taoufik; Levy, Michael; Schiess, Nicoline
Abstract: Objective: To determine the epidemiology and characteristics of transverse myelitis (TM) and neuromyelitis optica spectrum disorders (NMOSD) in Abu Dhabi, United Arab Emirates. Methods: Retrospective chart review at four large government‐run hospitals in Abu Dhabi between 2010 and 2016. Data collected included year of onset, presentation, laboratory results including aquaporin‐4 immunoglobulin G (IgG)/myelin oligodendrocyte glycoprotein IgG antibodies and the occurrence of any relapses. Results: A total of 46 individuals were identified. Of these, 23 (50%) were Emirati citizens. Within the overall group including pediatrics, the crude prevalence rate for monophasic TM was 1.0 per 100 000, and for NMOSD was 0.34 per 100 000. Incidence rates within the overall group for TM and NMOSD were 0.18 per 100 000 and 0.05 per 100 000, respectively. For Emirati citizens aged ≥20 years, the prevalence rate for monophasic TM was 2.46 per 100 000 and 1.76 per 100 000 for NMOSD, and the incidence was 0.57 per 100 000 and 0.17 per 100 000, respectively. The incidence of monophasic TM and NMOSD within the Emirati pediatric population (aged ≤19 years) was 0.18 per 100 000 and 0.06 per 100 000, respectively. The mean age of onset for monophasic TM was 36 years, and for NMOSD was 43 years. Nine patients had a positive aquaporin‐4 IgG or anti‐myelin oligodendrocyte glycoprotein IgG antibody result. Of the 30 participants with available laboratory cerebrospinal fluid analysis, 36.6% had elevated white blood counts (>5.0 × 10 6 /L), and 43% had elevated protein levels. A total of 19 participants had documentation of oligoclonal bands or IgG index, and just four (21%) had either oligoclonal bands or elevated IgG index. Conclusion: The present study describes the epidemiology and characteristics of TM and NMOSD among populations in Abu Dhabi. The adult prevalence rate for Emirati citizens was 2.46 per 100 000 for monophasic TM, and 1.76 per 100 000 for NMOSD. The overall incidence was 0.18 per 100 000 and 0.05 per 100 000, respectively. Abstract : This study examines the prevalence and incidence of monophasic TM and NMOSD in an adult and pediatric population in the UAE. The adult prevalence rate for Emirati citizens was 2.46/100 000 for Monophasic TM and 1.76/100 000 for NMOSD. Overall incidence was 0.18/100 000 and 0.05/100 000 respectively. Because healthcare in Abu Dhabi is free and Emiratis are required to be seen once at a government hospital, we believe this study to be an accurate representation of disease prevalence in the Abu Dhabi Emirate within the local citizen population.